Strategi Branding dan Digital Marketing dalam Membangun Brand Lokal: Studi Kasus Almaz Fried Chicken - Adi Iryanto; Oskar Judianto (Pantarei, 2026)
This study aims to analyze the branding and digital marketing strategies implemented by Almaz Fried Chicken, a local brand, to build awareness and accelerate market expansion in the digital era. The study used a qualitative approach with a case study method, through digital observation, in-depth interviews, and documentation analysis of brand activities on social media. The analysis was conducted thematically to identify marketing strategy patterns that include visual identity, brand narrative, and digital media utilization. The results show that the success of Almaz Fried Chicken is determined not only by product quality, but also by the strength of consistent visual branding and an effective digital communication strategy. A simple, modern, and easily recognizable visual identity plays a crucial role in increasing brand recall, while the narrative as a "proud local brand" can build emotional bonds with consumers. Furthermore, the use of social media platforms such as TikTok and Instagram through creative content, storytelling, and user-generated content has proven effective in creating virality and expanding market reach. However, this study also found that virality-based strategies face challenges in maintaining brand sustainability, particularly related to quality consistency, content innovation, and dependence on digital algorithms. Therefore, a more sustainable marketing approach is needed by holistically integrating cultural values, consumer experience, and digital strategy. This research contributes to the development of branding and digital marketing studies, particularly in the context of local brand growth in the digital economy era.